2021
DOI: 10.1111/adb.13047
|View full text |Cite
|
Sign up to set email alerts
|

A randomised, double‐blind study investigating the relationship between early childhood trauma and the rewarding effects of morphine

Abstract: Experiences of childhood trauma (abuse and neglect) are disproportionately higher in those with opioid use disorder (OUD). Childhood trauma may affect the reinforcing and rewarding properties of opioid drugs and responses to pain, potentially via developmental changes to the endogenous opioid system. This has been supported by preclinical research, yet this has not been investigated in non‐addicted humans. Physically healthy participants with either a history of severe childhood trauma or no previous history o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 66 publications
(122 reference statements)
2
17
0
Order By: Relevance
“…Overall, these results support the existence of substantial individual differences in the three mechanisms that have been linked to addiction. Importantly, while previous work had revealed abundant evidence on heterogeneity in approach/reward behavior, executive function and negative emotionality in addiction by investigating each functional domain separately [ 74 82 ], this is the first study to show that there are subgroups with differential functional profiles across these three domains.…”
Section: Discussionmentioning
confidence: 92%
“…Overall, these results support the existence of substantial individual differences in the three mechanisms that have been linked to addiction. Importantly, while previous work had revealed abundant evidence on heterogeneity in approach/reward behavior, executive function and negative emotionality in addiction by investigating each functional domain separately [ 74 82 ], this is the first study to show that there are subgroups with differential functional profiles across these three domains.…”
Section: Discussionmentioning
confidence: 92%
“…68 In humans, those exposed to ACEs show a stronger dopamine response to drugs, report greater pleasurable effects (eg euphoria), greater desire for more, and fewer negative effects of opioids compared to those non-exposed to ACEs, as well as a positive association between the number of adverse events in adulthood and dopamine response. 68,69 These alterations may potentially enhance the rewarding effects of substances, increasing the risk of transitioning from controlled to Substance Abuse and Rehabilitation 2022:13 https://doi.org/10.2147/SAR.S341818 DovePress 93 Dovepress compulsive use of substances, and help to explain severity of those presenting with substance use disorder with a history of ACEs. 63,68 Indeed, differences in function and structure of these brain regions have been shown to mediate the relationship between ACEs and subsequent alcohol dependence.…”
Section: The Stress Responsementioning
confidence: 99%
“…The risk factors documented are multiple, ranging from genetic influences [10][11][12][13]; personality risk factors, such as impulsivity or the tendency toward risky behavior [14], including use of other substances; traumatic experiences, including early life adversity and family history of substance use disorders [15,16]; demographic characteristics, including exposure to opioids at young age and being male [17,18]; subjective experiences at first opioid use, such as euphoria [19]; nonmedical opioid use, including the use of opioids to get high, improve sleep, decrease anxiety [20]; medical and psychiatric comorbidities, particularly pain conditions or incidence of other substance use disorders [21]; surgical procedures, either minor or major [22,23]; higher and prolonged doses of opioids used [21]. diagnosis, prevention, and treatments.…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies have shown that high ratings of opiate liking, as well as other subjective effects to first exposure to opioids (e.g., good mood, happy ratings), increase liability to dependence and misuse, compared to dysphoria and sedation [19, 29]. Laboratory studies also allow us to capture hard-to-measure characteristics associated with OUD, such as impulsivity [30], adverse childhood events [31], and trauma [15, 16]. Notably, laboratory studies allow for the direct control of environmental variables, including the ability to administer certain doses of opioids under controlled settings [32], akin or generalizable to the data collected from “real-world” settings, such as that from hospital cohorts [33, 34].…”
Section: Introductionmentioning
confidence: 99%